KETERKAITAN CYCLOOXYGENASE (COX)-2 TERHADAP PERKEMBANGAN TERAPI KANKER - Fajrin, Fifteen Aprila (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
The growth of tumors is caused by imbalances between the rates at which cells are produced through cell division and the rate at which they die through a natural cell death process known as programmed cell death (also referred to as apoptosis). Problems in apoptosis mechanisms also contribute to therapy resistance, making tumors more difficult to kill with radiation or chemotherapy. It is important therefore to understand why tumors become refractory to apoptosis and to devise strategies for restoring proper function to cell death pathways in tumor cells. Recently it has been discovered that cyclooxygenase-2 (COX-2) have a relationship with apoptosis pathway. Higher levels of COX-2 have been reported in some kinds of cancer. One of the roles of COX-2 in tumor development is its positive effect on the survival of tumor cells. The goal of this project is to provide review insights into the role of COX-2 in cancer. We will explore whether COX-2 inhibitors can shut off survival genes in cancer cells, and we will study how COX-2 affects the programmed cell death machinery of cancer cells. Understanding the mechanisms by which COX-2 contributes to cancer development will reveal to what extent this enzyme is an important target in the chemoprevention and treatment of cancer.